تحسين وثوقية عمل أنظمة الحماية من الحريق في المنشآت الصناعية باستخدام المتحكمات المنطقية القابلة للبرمجة PLC - قاسم محمد; الإبراهيم حسن (Latakia University Journal -Engineering Sciences Series, 2019)
تعاني منظومة الحماية من الحريق في منشأة صناعية خاصة مصممة باستخدام دارات تحكم تقليدية, من مشاكل كثيرة ترتبط ببنيتها التصميمية(زمن الاستجابة), وظروف الاستثمار(الوثوقية), إضافة لتعدد الكتل الموجودة في التصميم, والحجم الكبير لها, وهي مؤشرات على انخفاض وثوقية هذه المنظومة وفعاليتها. و يناقش البحث التقانات الحديثة التي بدأت تحل محل المنظومات القديمة في المنشآت الصناعية, والحلول التي تقدمها للتغلب على المصاعب الكثيرة التي كانت تُواجَه خلال تصميم هذه المنظومات, ووضع خوارزميات التحكم المطلوبة للعمل, وتوظيف المتحكمات المنطقية القابلة للبرمجة لأتمتة الأعمال المختلفة في المنشآت الصناعية, حيث تم تحليل آلية عمل المنظومة ووضع المخططات السلمية اللازمة(النموذج الرياضي المنطقي), التي تحاكي عمل المنظومة في الزمن الحقيقي، كما تم تصميم القاعدة المادية التي تؤمن العمل المؤتمت للمنظومة وتسمح بمراقبة الحالة الفنية لها واختبار جاهزيتها، كما تم اختيار المتحكم المنطقي باعتماد خوارزمية خاصة تأخذ بعين الاعتبار المواصفات الفنية ومواصفات المستخدم، وتجهيز دارات الملاءَمة المطلوبة للربط مع المتحكم المنطقي القابل للبرمجة. The firefighting system in any private industrial establishment using the traditional control circuits suffers many problems related to its structural design (time of response) and the investment conditions (reliability), besides the existence of numerous big-size masses in the design. All of these are indications to the decrease in the efficiency and the reliability of this system. This paper discusses the modern technologies that started to replace the old ones in the industrial establishments, and the solutions these modern technologies present to overcome the numerous problems we used to face during the process of designing these systems, to establish the necessary control algorithms for work, and to employ programmable logical controllers in order to automate the different tasks in the industrial establishments. In this respect, the mechanism of the system was analyzed and the necessary ladder diagrams were put (mathematical logical model), the thing that simulates the performance of the system in actual time. Also, the material base that provides the automated work of the system was designed, the thing that helps in observing its technical conditions and testing its readiness. We have chosen the programmable logical controller by the use of special algorithm that takes into consideration the technical specifications, user descriptions and the preparation of the proper circuits to connect with the programmable logical controller.